Added resistance and seakeeping performance of trimarans in oblique waves. (15th November 2020) - Gong, Jiaye; Yan, Shiqiang; Ma, Qingwei; Li, Yunbo
Abstract: Trimaran added resistance and seakeeping performance in oblique waves with strong nonlinearity are rarely investigated. This paper presents the numerical investigations on them by applying a hybrid method, called the QaleFOAM. This method can simulate a trimaran moving in a large wave field, considering viscous effects and dealing with violent wave-structure interaction (WSI). The numerical method is validated by experimental data for a trimaran moving in waves. Various cases are investigated with different wave steepness, different wavelengths, different forward speeds and different wave incident angles to study the properties and characteristics of the added resistance and seakeeping performance of a trimaran. The results demonstrate that the variational trend of the added resistance and motion amplitudes of the trimaran in waves is significantly affected by the wave steepness and wave incident angles and different from those of traditional mono-hull ships. Highlights: A systematic study on the added resistance/seakeeping performance of trimarans in oblique waves of different parameters. Directly modelling the advancing of the trimaran in waves by using a robust hybrid model, QaleFOAM. The added resistance and motion amplitudes of the trimaran are significantly affected by the wave steepness and wave incident angles. Two approaches (directly modelling or inputting ship speed and waves at inlet) for forward ship in waves leading to considerable difference.